Aspekte van ’n Christelike perspektief op fasette van die Geskiedwetenskap en die beoefening daarvan in ’n veranderende Suid-Afrika - Eeden, Elize S. van (Koers, 1996)
Aspects of a Christian perspective on some facets of History as a discipline and its practice in a changing South Africa Within the framework and dynamics of a currently changing South Africa, not only History as a practised discipline hul historians too - especially Christian historians are increasingly criticised from various quarters and/or faced with totally new obstacles and questions. Although criticism in this sense constitutes nothing new perse, the f undamental character of changes sweeping the country (e.g. democratization, nation building, truth and reconciliation, societal restructuring) and the historio-political legacy of the recent past, re-accentuated the criticism that South African historiography has consistently proved to be subservient of a political ideology. The objectives of this article are to highlight some former historical trends and current tendencies in Christian perspectives of the past and to discuss the question of how Christian historians and Christian History teachers can interact in a responsible and careful way with their subject by avoiding misrepresenting the truth and of becoming (again?) the servants of just another ideology.